Numerical study on the hydrodynamic performance of a symmetrical dual-chamber oscillating water column wave energy converter - Li, Meng; Yang, Zehua; Wu, Rukang; Wu, Bijun (Frontiers in Energy Research, 2023)
In this study, a novel floating oscillating water column (OWC) wave energy converter (WEC) with dual chambers is proposed, and its hydrodynamic performance and primary energy conversion characteristics are investigated by numerical calculation. It consists of a floating body and two long vertical pipes opening downward at the bottom, forming dual chambers at the top. These two rectangular pipes are fixed to the front and back ends of the buoyancy tank with the same width, and it can be regarded as an oscillating single floating body as a whole. Under the action of the incident wave, the WEC captures wave power by the heave motion and relative motion of the pipe and the water column in it to form an oscillating water column, outputting pneumatic power. The geometry size of the vertical pipes is optimized by comparing the hydrodynamic performance and capture width ratio (CWR) of the WEC models with several rectangular pipes of different sizes. The calculation results show that increasing the draft, which is positively correlated with the total mass of the WEC model, increases its optimal response period. By comparing the numerical calculation results of the hydrodynamic performance and CWR of the WEC models with three kinds of floater bottom shapes, semi-cylindrical, sharp-bottomed, and flat-bottomed, it is found that the flat-bottomed model has the best capture performance.